Shén (神) in Modern Chinese - Liu Hsiu-Ying (Sciendo, 2018)
In modern Chinese, a new degree adverb shén 神 is emerging. Expressions such as shénhăochī 神好吃 and shényǒuqù 神有趣 are found in colloquial Chinese, and they even appear as headlines to get readers’ attention. Shén originally refers to the dominator and creator of the universe. In modern Chinese, along with the original meaning, people frequently use shén to modify things (e.g., shén jīyīn 神基因) or actions (e.g., shén huí 神回). How many senses does shén have? How did shén derive the use of degree adverb? The paper targets on shén in modern Chinese, aiming to study its senses, to work out the relations among the various usages, and to find out how it generated the use of degree adverb. The conclusion shows that the senses of shén were derived from its original meaning either directly or indirectly through reanalysis, inference, metaphorization, and metonymization. The use of degree adverb was generated through metaphorization and reanalysis.